2020
DOI: 10.7240/jeps.697779
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Anatomical Features Study of the Some Medicinal Rumex Species Distributed in Turkey

Abstract: Distributed in Turkey Rumex crispus L., Rumex patientia L., anatomical features of Rumex obtusifolius species were comparatively investigated in this study. For anatomical studies, cross-sections were taken from root, stem and leaf. In addition, superficial sections were taken from the leaf and stomata index and stomata features were determined. Druse crystals were found at the root of the R. obtusifolius. The radial-shaped vascular bundles in the root of R. crispus had 4-5 arms. Glandular hair was found only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In a normal situation, inflammation activates a variety of protein kinases, including AKT/PI3K, MAPK, and JAK, as well as the families of protein kinases associated with the members of these protein kinase families, with the goal of modifying metastasis progression [ 104 ]. Several Rumex species, including R. vesicarius, R. nepalensis , and R. patientia , have been reported to have anti-inflammatory properties [ [105] , [106] , [107] , [108] ]. A study found that R. dentatus polyphenol-rich extract increased PPARc expression while suppressing inflammation and oxidative stress [ 109 ].…”
Section: General Pharmacology Of Rumex Dentatusmentioning
confidence: 99%
“…In a normal situation, inflammation activates a variety of protein kinases, including AKT/PI3K, MAPK, and JAK, as well as the families of protein kinases associated with the members of these protein kinase families, with the goal of modifying metastasis progression [ 104 ]. Several Rumex species, including R. vesicarius, R. nepalensis , and R. patientia , have been reported to have anti-inflammatory properties [ [105] , [106] , [107] , [108] ]. A study found that R. dentatus polyphenol-rich extract increased PPARc expression while suppressing inflammation and oxidative stress [ 109 ].…”
Section: General Pharmacology Of Rumex Dentatusmentioning
confidence: 99%